Rediscovery and redescription of the Malagasy dwarf gecko Lygodactylus klemmeri - Puente, Marta; Raselimanana, Achille P.; Vences, Miguel (Zootaxa, 2005)
Lygodactylus klemmeri Pasteur, 1964 is a small diurnal gekkonid lizard described on the basis of a single male specimen from Antsingy forest in western Madagascar, deposited in the Paris museum. This specimen could not be retrieved during recent years in the Paris collection and might be lost. Hence, the only existing information on this gecko is the original description and some subsequent remarks on the holotype by G. Pasteur. We here report on new material of L. klemmeri from the collection of the University of Antananarivo, Madagascar, and provide a comparison to published morphological data of the holotype.